Analysis of the structure of salaries of public sector workers for strategic planning purposes An analytical study in the general body of groundwater - R. S. Al-Madhidi, Raqeeb; L. Said, . Abdul Salam (Journal of Economics and Administrative Sciences, 2020)
The research discusses the problem of salaries in the public sector in terms of the process of analyzing its structure and the possibility of benefiting from the information provided by the analysis process for the strategic planning process, and the General Authority for Groundwater has been adopted and one of the formations of the Ministry of Water Resources, which is centrally funded, to represent the salary structure of its employees (1117) employees be a field of research, as the salary structure in it was analyzed for the period between (2014-2019) using the quantitative approach to analysis and by relying on a number of statistical tools in the analysis process, including mathematical circles, upper limits, lower limits, percentage and rate of change, and the research reached a set of conclusions, including knowledge of the behavior of salary movements, the size and distribution of detailed spending and its concentration, giving a clear vision about the nature of the use of the country's financial and human resources as far as the matter is concerned with research, analysis of the strategic dimension resulting from decisions to reduce spending, and the contribution of detailed data and information resulting from the analysis process in developing appropriate policies and strategies. The process of analyzing salaries and according to the approved tables of analysis tables, contributed to the disclosure of the failures in salaries and its structure, whether in the technical side of the structure or the administrative and accounting aspects related to public operational spending and the preparation and distribution of workers, and their impact on the strategy developed and in a manner that leads to the achievement of maximum benefit resources and capabilities and directing them towards optimal use.